STRATEGI PEMASARAN TRANSAKSIONAL PRESPEKTIF ISLAM - Achmad Ilham Syiham Muzakky; Sulistyowati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Transactional marketing is a strategy focused on achieving short-term sales transactions through promotional tools such as discounts, bundling, and other incentives. While effective in increasing sales volume, transactional marketing is often criticized for neglecting long-term customer relationships. The Islamic perspective offers an alternative approach in implementing this strategy by integrating Sharia principles such as wisdom (hikmah), need, halal, welfare (falah), and mutual consent. By applying the characteristics of Islamic marketing, including rabbaniyyah (theistic), akhlaqiyyah (ethical), al-waqi’iyyah (realistic), and insaniyyah (humanistic), transactional marketing can become more ethical, inclusive, and have a positive impact on society. The application of Sharia principles in transactional marketing not only brings financial benefits but also creates fair, transparent business relationships that prioritize the welfare of the community. Therefore, Islamic marketing in the transactional context becomes a sustainable business solution, aligned with the principles of justice and goodness in Islam.